Determination of acrylamide in toasts using digital image colorimetry by smartphone. (November 2022) - Sáez-Hernández, Roberto; Ruiz, Pablo; Mauri-Aucejo, Adela R.; Yusa, Vicent; Cervera, M.L.
Abstract: A digital image colorimetric approach was developed using a smartphone as a detection device to study acrylamide concentration in homemade toasts. Different slices of white bread were toasted, their resulting colour was captured with the smartphone, and the acrylamide concentration in the samples was determined by LC-MS/MS. From that information, a regression model was built in order to obtain an estimation of the total acrylamide content in the toast from an image. Results indicated that R (from RGB colour space) and h* (hue, from CIE L*C*h*) worked well as predictors, following a linear and a polynomial response, respectively. With this approach, the colorimetric analysis allowed to estimate the acrylamide concentration in the samples in the range of 20–200 μg kg −1, clearly identifying those samples which were below the recommended value (50 μg kg −1 ) from the ones above it. Additionally, a more exhaustive colorimetric study was carried out on different fractions of the toasts to investigate the suitability of image colorimetry in the acrylamide control in daily consumed products. Overall, this works proves the applicability of smartphones for food control and analysis, allowing to obtain quantitative estimations of chemical parameters of concern. Graphical abstract: Image 1 Highlights: Acrylamide content was studied in home-made wheat bread toasts using LC-MS/MS. Colour of samples was analysed with an smartphone camera. Predictive models were created to correlate acrylamide content and color parameters. Hue and R (from RGB) showed good correlations with total acrylamide content. An easy approach to estimate the content of acrylamide in home toasts is developed.